The Effectiveness Test of Ethanol Extract 96% Garlic Pubber Skin as Anti-Aging - Mustaruddin (PT Inovasi Pratama Internasional, 2022)
Aging is a process experienced by the human body where the function of body parts becomes reduced, for example, the skin is getting thinner and then wrinkles appear. Premature aging of the skin occurs due to photoanging by UV radiation and some bad living habits. In reducing the signs of aging on the skin, antioxidants are needed to protect the skin from damage caused by oxidation so that it can prevent premature aging. Antioxidants can be enzymes (eg superoxide or SOD, catalase, glutathione peroxidase), vitamins (eg vitamins E , C, A ) and other compounds such as flavonoids, albumin, bilirubin, ceruloplasmin and others. One of the antioxidants found in nature is garlic peel . Garlic peel has been shown to have many benefits including, containing flavonoids, polyphenols, alkaloids and tannins, and it is this content that proves garlic skin contains separate antioxidants.